1998
DOI: 10.1161/01.hyp.32.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nitric Oxide and Prostaglandins in the Long-term Control of Renal Function

Abstract: Abstract-Previous studies have reported evidence of an important interaction between nitric oxide (NO) and prostaglandins in the acute regulation of renal function. The objective of this study was to determine in conscious dogs whether the renal effects of the prolonged administration of a cyclooxygenase inhibitor are enhanced when NO synthesis is reduced. Meclofenamate infusion (5 g ⅐ kg Ϫ1 ⅐ min Ϫ1 ) during 4 consecutive days (nϭ8) elicited a continuous decrease (PϽ0.05) in renal blood flow and plasma renin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
32
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 29 publications
7
32
0
Order By: Relevance
“…21 Prolonged COX-2 inhibition in dogs with normal sodium load did not induce changes in GFR and elicited a mild decrease in RBF. When comparing the renal hemodynamic effects of a nonselective COX inhibitor 10,11 with those reported in the present study, it can be proposed that the metabolites derived from both COX isoforms are involved in the regulation of renal hemodynamic. This notion is supported by results obtained in healthy adults 17 and suggests the preferential use of selective COX-2 inhibitors for treatment of inflammatory processes, as opposed to nonselective inhibitors, when sodium intake is normal.…”
Section: Figurementioning
confidence: 64%
See 3 more Smart Citations
“…21 Prolonged COX-2 inhibition in dogs with normal sodium load did not induce changes in GFR and elicited a mild decrease in RBF. When comparing the renal hemodynamic effects of a nonselective COX inhibitor 10,11 with those reported in the present study, it can be proposed that the metabolites derived from both COX isoforms are involved in the regulation of renal hemodynamic. This notion is supported by results obtained in healthy adults 17 and suggests the preferential use of selective COX-2 inhibitors for treatment of inflammatory processes, as opposed to nonselective inhibitors, when sodium intake is normal.…”
Section: Figurementioning
confidence: 64%
“…10,11,15 PRA and PAC were measured using commercial RIA (DiaSorin). Urinary concentration of PGE 2 , 6-keto-PGF 1␣ , TXB 2 , and 11-dehydro-TXB 2 were measured using commercial EIA kits (Cayman Chemical).…”
Section: Analytic Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…23 It is now appreciated that NO, a reactive oxidation product of nitrogen, is produced normally by many cell types, including endothelial cells, and has functions ranging from neurotransmission to vasodilation; also, there is a complex association between PGs, NO, and cytokine pointing to the regulation of the inflammatory process: proinflammatory cytokine interleukin-1␤ (IL) stimulates inducible nitric oxide synthase (iNOS) mRNA, protein, and NO production in neonatal ventricular myocytes 34 and, in other types of cells, it also activates phospolipase A 2 , which liberates AA (Figure 1), but it also induces the cyclo-oxygenase isoform (COX), 17 and NO has been shown to directly stimulate COX activity and AA metabolites other than COX products, possibly being products of the lipoxygenase pathway, which are involved in IL regulation of iNOS 17 (Figure 1). Moreover, it has been suggested that the renal vasoconstriction and antinatriuretic effects induced by a prolonged infusion of a COX inhibition are significantly enhanced when NO synthesis is blocked; 20 additionally, a chronic NO inhibition may contribute to systemic HT and play a pivotal role in the development of renal structural injury. Finally, the association of NO-PGs contributes to the regulation of RBF and renal funcJournal of Human Hypertension tion and structure, suggesting that both NO and PGs control a similar percentage or rat renal papillary blood flow, but NO seems to be more important than PGs as a mediator of the pressure-blood flow relationship; 21,30,34 also, a relationship between bradykinin receptors and PGs has been suggested, and they have a steroidogenic effect.…”
mentioning
confidence: 99%